PENGARUH KURANGNYA KASIH SAYANG ORANG TUA SEBAGAI FAKTOR PEMICU MASALAH PERILAKU PADA ANAK USIA DINI DI TK AISYIYAH BUSTANUL ATHFAL 5 BATAM KOTA - Thasari, Chania Wafiq (Hamka Ilmu Pendidikan Islam, 2025)
Lack of parental attention and emotional affection can be a cause of behavioral problems in early childhood. This study aims to explain the impact of insufficient parental affection on the behavior of early childhood children at TK Aisyiyah Bustanul Athfal 5 Batam City. The findings indicate that children who do not receive adequate affection tend to exhibit mild aggressive behavior, tantrums, irritability, difficulties in emotional regulation, and limited ability to interact with peers as expressions of unmet emotional needs. Therefore, it can be concluded that insufficient parental affection has a significant impact on the emergence of behavioral problems in early childhood, highlighting the importance of warm and consistent parental emotional involvement to support optimal emotional and behavioral development.